English For Specific Purposes in the Aviation - Kiyasova Ra’no Malikovna; Artikov Jasurbek Alisherovich (Peerian Journals Publishing, 2022)
“Aviation English” is not only confined to pilots and air traffic controllers it also refers to English on general terms in aeronautical and/or aviation universities. It can be designed as integrated ESP (English for Specific Purposes) curricula for students in the fields of aeronautics and/or aviation. Learners of ESP are supposed to master the vocabulary in their specific discipline as well as the English language skills. This paper explores the possibility of establishing Aviation English as an ESP specialty in aeronautical and/or aviation colleges and universities. Needs analysis has been made and curricula designed for an integrated course of study in the Uzbek contexts, so that learners of ESP can learn the target language more effectively and meet the standards set by the International Civil Aviation Organization (ICAO). It reconsiders the ESP theories and aims to develop a possible approach to ESP teaching more suitable for the Uzbek learners
Keywords: Aviation English; needs analysis; curriculum design; airports